Intentions to trust and share online health rumors : an experiment with medical professionals - Chua, Alton Yeow Kuan (2019)
With the rise of fake news and doctored narratives on the Internet, research on online rumors is growing. Previous works often dealt with either individuals' trust in rumors or their willingness to share. Juxtaposing both in the same study, the aim of this paper is to investigate medical professionals' intentions to trust and share online health rumors as a function of their personal involvement, the rumor type, and the presence of counter-rumors. Personal involvement refers to individuals’ perceived relevance of a rumor. Two common types of rumors include dread and wish. Counter-rumors are messages that debunk rumors. A within-participants experiment was conducted with 60 participants, divided evenly among doctors, nurses and medical students, each of whom was exposed to eight cancer-related rumors. Rumor type and the presence of counter-rumors were induced. Personal involvement, intention to trust, and intention to share were measured using a questionnaire. Results showed that personal involvement compelled intentions to trust and share. Dread rumors triggered intentions to trust and share more than did wish rumors. The presence of counter-rumors lowered intention to trust, but not intention to share. Moreover, rumor type moderated the relation between personal involvement and intentions to trust and share.